Regional Differences of Productivity in European Agriculture - Daniel, Arnold (Review of Economic Studies, 1944)
Journal Article Regional Differences of Productivity in European Agriculture Get access Arnold Dániel Arnold Dániel Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 12, Issue 1, 1944, Pages 50–70, https://doi.org/10.2307/2296013 Published: 01 January 1944